Study of the Charge Carrier Diffusion of a Silicon Solar Cell in the Unsteady Regime Under Multispectral Illumination: Effect of Frequency and Recombination Rate - Sene, Mamadou Bamba; Boiro, Mountaga; Kouyaté, Mamadou; Diao, Amadou; Faye, Alioune; Mbow, Cheikh (European Journal of Applied Sciences, 2024)
In this paper, the three-dimensional diffusion of photogenerated charge minority carriers in a polycrystalline silicon solar cell under multispectral illumination in the unsteady regime has been investigated by a numerical method; in order to optimize photocell efficiency. The influence of grain illumination frequency and recombination rate at grain boundaries on the charge carrier density and photocurrent density of a polycrystalline silicon solar cell was also investigated. From the continuity equation for minority carriers in the base, expressions for photocurrent density as a function of junction recombination rate have been derived for different values of grain size and grain boundary recombination rate. The influence of time on the minority carrier density and on the electrical power delivered by the solar cell was presented. The photocurrent density was studied as a function of the recombination rate. The aim is to carry out a numerical resolution, making fewer simplifying assumptions to bring the study closer to reality compared with other resolution methods.